Modified Maximal Levator Palpebrae Superioris Shortening in Correcting Congenital Severe Ptosis in Children. Issue 5 (November 2021) - Liu, Ninghua; He, Aijuan; Wu, Dan; Zhang, Jing; Song, Nan
Abstract : Objective: This study aims to evaluate the clinical effect of modified maximal levator palpebrae superioris shortening method for severe congenital ptosis. Methods: A retrospective case series was performed including 66 eyes from 62 patients who underwent modified maximal levator palpebrae superioris shortening surgery to treat severe congenital ptosis between February 2015 and November 2018. Preoperative and postoperative margin reflex distance 1 and levator muscle function were recorded. The surgical results were graded as good, satisfied, and poor for functional and cosmetic improvement of the eyelids, and the incidence of complications was also documented. Results: The mean patient age at the time of surgery was 4.6 ± 1.8 years (2–9 years), and the mean follow-up time was 36.3 ± 14.1 (12–55 months). A mean significant improvement in margin reflex distance 1 and levator function after operation was noted ( P < 0.01). The eyelid height and symmetry were satisfied in 59 patients, with success rate of 95.2%. For the patients in the levator function (⩽2 mm) group, the success rate was 87.5%. Moreover, the levator function (⩽2 mm) group had a higher rate of poor results than levator function (2–4 mm) group (12.5% vs 2.2%). Overcorrection (6.5%) and eyelid fold deformity (11.3%) were the most frequent postoperative complications. Conclusion: Modified maximal levator palpebrae superioris shortening was effective and endurable in the treatment of severe congenital ptosis with poor levator function, including in patients whose levator function was less than 2 mm. Abstract : Supplemental digital content is available in the text.